Heart rate as an independent risk factor for the development of cardiovascular diseases - Czarnecka, Danuta; Kloch-Badełek, Małgorzata; Wiliński, Jerzy; Kusak, Piotr (Przewodnik Lekarza/Guide for GPs, 2008)
Epidemiological and pathophysiological data support the idea of slowing down the heart rate. It has been confirmed that higher heart rate is an independent risk factor for cardiovascular death irrespective of other classical risk factors. Methods of heart rate reduction such as beta-blockers or calcium antagonist treatment are associated with various complications. A selectively reducing heart rate medication does not yet exist in daily practice. Ivabradine is the first modern drug selectively reducing heart rate by inhibiting If ion channels of the sinus node. The selective mechanism of action of ivabradine introduces new perspectives in the treatment of coronary artery disease and other cardiovascular diseases.